Changes in the Surface of Red Blood Cell Membranes after Blood Loss and Their Correction with Laser Irradiation - V. V. Moroz; A. K. Kirsanova; I. S. Novoderzhkina; Ye. K., Kozlova; P. Yu. Borshchegovskaya; U. A. Bliznyuk; V. V. Aleksandrin; A. M. Chernysh (Общая реаниматология)
Objective: to reveal changes in the membrane surface microrelief during hypotension and after blood reinfusion and a possibility of correcting these impairments with laser irradiation (LI). Materials and methods. Experiments were carried out on anesthetized male rats weighing 450 g. The model of a terminal state was one-hour hypovolemic hypotension (mean blood pressure 45 mm Hg), followed by exsanguinated blood reinfusion. Two groups of experiments were made. These were control and experimental; in the latter laser irradiation was performed for 2 minutes an hour after blood reinfusion. Rat blood smears were examined on an atomic force microscope 5 and 60 minutes after blood loss and 1 and 3 hours after blood reinfusion. Results. The experiments have shown that after blood reinfusion the activated lipid peroxidation processes increase the size of a red blood cell and change its shape and its membrane surface relief. By producing an antioxidant effect, LI restores the permeability of red blood cell membranes and their surface ultrastructure. Key words: blood loss, red blood cells, membrane, lipid peroxidation, atomic force microscope.